Improving the Ability of the Students with Learning Difficulties to Use Space by Making Use of Bottle Cap Creation (A Single Subject Research Conducted in Grade III of SDN 15 Ulu Gadut) - Fitri Handayani (Universitas Negeri Padang, 2016)
ABSTRACTFitri Handayani. 2016. Improving the Ability of the Students with Learning Difficulties to Use Space by Making Use of Bottle Cap Creation (A Single Subject Research Conducted in Grade III of SDN 15 Ulu Gadut). Thesis.Undergraduate Program of Special Study Program of the Faculty of Education of State University of Padang. This research was conducted based on the problems found at SDN 15 Ulu Gadut Padang indicating that a student with learning difficulties had problem to use space in writing. This research, therefore, was intended to increase the ability of the student with learning difficulties to apply space in writing by making use of bottle cap creation. This was a Single Subject Research which applied A-B-A design. The data gathered were analyzed by using visual analysis of graphic. The subject of the research was a student with learning difficulties in grade III. Through this research she was required to write several sentences with appropriate use of space. The number of the sentences written in each meeting was 10. The variable was measured by using percentage technique. The result of the research showed that the use of bottle cap creation could increase the ability of the student with learning difficulties to use space in writing by making use of bottle cap creation. In the baseline condition (A1) that consisted of seven observations, the student’s ability was in the range of 12% and 18%. In the intervention condition (B) that consisted of ten observations and through which intervention of bottle cap creation was given, the student’s ability was 92%. In the Baseline condition (A2) that consisted of five observations, the student’s ability was in the range of 88% and 94%. Based on these results, it was concluded that the use of bottle cap creation could increase the ability of the student with learning difficulties to use space in writing. Therefore, it was recommended to the teachers to use bottle cap creation to increase the ability of the students with learning difficulties to use space in writing. Keyword: use space in writting, the student with learning Difficulties,media of bottle Cap Creation.